Strategic Approach to Strengthen one Dentist's Competitive Advantage in the Dental Clinic Industry in Indonesia - Rafie Bhijak Saloka (Journal of World Science, 2025)
This study examines the strategic approach to improve SATU Dental's competitive position as the largest mid-market dental clinic operator in Indonesia. It aims to understand the effects of regional demographics, competition, and patient behavior on clinic performance and propose strategic initiatives to enhance competitiveness. The research combines quantitative and qualitative methods. The quantitative part analyzes revenue, patient volume, and growth across nine areas, while the qualitative part involves interviews with internal stakeholders. Data were analyzed using VRIO, PESTEL, Porter's Five Forces, and SWOT/TOWS frameworks. Results show regional performance differences. Bogor and East Jakarta have high growth due to middle-class demographics and moderate competition; North and Central Jakarta have strong revenues but slow growth from mature patient bases. Depok and Tangerang show low performance due to price sensitivity and limited accessibility. Qualitative analysis highlighted four themes: strategic alignment, financial management, operational contingencies, and clinical practice. VRIO identifies brand reputation and service standardization as lasting competitive advantages. PESTEL indicates a positive macro environment with middle-class growth and digitalization, tempered by exchange rate fluctuations and low-cost competition. The SWOT/TOWS analysis suggests three strategic directions: (1) Service Differentiation through Clinical Excellence and Digital Integration, (2) Human Capital and Capability Development, and (3) Operational Standardization and Performance Progress. In conclusion, SATU Dental's strategic competitiveness relies on balancing standardization with localization, targeting growth in high-potential areas, and innovating services in mature markets.